Using informative assessments towards effective literacy practices - Ortlieb, Evan; Cheek, Earl H. (Literacy research, practice and evaluation,, 2012)
Utilizing Informative Assessments towards Effective Literacy Instruction offers research driven solutions to improving student literacy success through the exploration of advancements in literacy assessment and instruction. As the first volume in the series, Literacy Research, Practice, and Evaluation, distinguished authors share a comprehensive portrayal of why assessments are necessary, how to select appropriate assessments, and how to effectively use data for curricular planning and instruction. By addressing concerns before, during, and after literacy instruction with research-based instructional techniques embedded within the chapters, readers garner rich perspectives on literacy assessment that can immediately impact their effective teacher practices. This text is founded on the principle that praxis, or the combination of research with practice, should be the ultimate goal of educational missions and visions alike. It provides a fresh examination of current issues and trends in literacy assessment salient to novice and experienced educators alike.